Covid-19 Effect on Business Performance SMMES Perspectives in a South African Context - Vukile Mlungisi Mkhonza; Portia Pearl Siyanda Sifolo (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: There is lack of enough empirical and conceptual studies of business performance among Small Medium Enterprises (SMEs), not only in South Africa, but the African continent. Design/methodology/approach: A quantitative study was conducted with the use of an online survey distributed to the sample of 169 participants who were SMME owners and management in Johannesburg CBD. Findings: The results showed that most SMMEs owners used strategic planning techniques which helped improve their performance. Formalizing SMMEs strategic planning process and taking advantage of technology is imperative for business performance. However, these results were based on a single point in time; therefore, longitudinal research will be able to provide new insight on how strategic planning can influence the performance of SMMEs. Research limitations/implications: This research study sought to investigate the Small Micro Medium Enterprises (SMMEs)’ perspective on business performance during Covid-19 in Johannesburg Central District Municipality (CBD). Practical implications: The research focused mainly on SMMEs operating in Johannesburg CBD Paper type: Research Paper